Aprendizados da experiência chinesa : sobre as relações de Estado numa transição ao socialismo - Gomes, Helder (2016)
This Doctoral Thesis presents the debate on the state relations in a transition to socialism in two complementary perspectives. The idea is to leave a clear outline of conception of the character of the State form, in the projection of a post-capitalist transition in both aspects of their nature as regarding their forms of intervention. At the same time, the work comes to identifying elements that could corroborate for understanding the relations of the State in the early stages of a transition from a concrete experience of implementing a socialist construction project. Thus, the text is centered to indicate a possible way to interpretation, which may contribute to the understanding of the character of the State in the early decades of transition to socialism, with the fundamental base of support the accumulation of dialectical knowledge on the subject and some of the references dealing with the construction process of the People's Republic of China. In this particular case, it was evident that despite the development of a strategic project, long-term, the internal circumstances and the external imperialist pressure, in every moment, demanded tactical reorientation that often were changing the plans of deployment of pace initials, extending the outlook concerning the duration of Chinese transition to socialism. Hence the statement about the need to reach a certain spread of the possibility of progress in alternative forms of collectivization of production and the abolition of private property to project the consolidation of socialism. This means that the revolution should be a process permanently in at least two senses: allowing a continuous process of renewal of the living forces of the revolutionary movement in the social fabric, seeking a rural-urban unit; but at the same time creating the conditions for international solidarity in promoting the popular mobilizations of transforming nature in as many countries as possible. Only in this way a spread of the socialist world revolution could be permanent.